2011
DOI: 10.3382/ps.2011-01465
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with the humoral innate immune response in chickens were confirmed in a cross between Green-Legged Partridgelike and White Leghorn

Abstract: Natural antibodies (NA) create a crucial barrier at the initial steps of the innate humoral immune response. The main role of NA in the defense system is to bind the pathogens at early stages of infection. Different pathogens are recognized by the presence of highly conserved antigen determinant [e.g., lipopolysaccharide (LPS) in gram-negative bacteria or lipoteichoic acid (LTA) in gram-positive bacteria]. In chickens, a different genetic background of NA binds LPS and LTA antigens, encoded by different QTL. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…; Slawińska et al . ). The current study showed that the selected SNPs were located within regions originally suggested by those linkage analyses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Slawińska et al . ). The current study showed that the selected SNPs were located within regions originally suggested by those linkage analyses.…”
Section: Discussionmentioning
confidence: 97%
“…; Slawińska et al . ). Validated QTL on the GGA9, GGA14 and GGA18 chromosomes were fine mapped using two statistical tools: meta QTL analysis and joined QTL analysis (Slawinska & Siwek ).…”
Section: Introductionmentioning
confidence: 97%
“…The remaining eight QTLs for the antibody response against IBV were novel and specific QTLs in this study. They were not only different from the QTLs for the antibody response against Newcastle disease virus, they also differed from the QTLs for immune responses against other stimuli, such as Brucella abortus (Zhou et al, 2003), E. coli (Yunis et al, 2002a,b), keyhole lympet hemocyanin (Siwek et al, 2003), sheep red blood cells (Dorshorst et al, 2011), infectious bursal disease virus (Ewald et al, 2007) and lipoteichoic acid (Slawinska et al, 2011). Nevertheless, all the QTLs linked to the antibody response against IBV were not independent of body weights in chickens ( Supplementary Table 3), and birds with the favored genotype of the QTLs linked to the antibody response against IBV had significantly lower body weights (unpublished results).…”
Section: Comparison With Other Association Studies For Immune Responsmentioning
confidence: 87%
“…In recent times, it has been used to study the genetic background of general immune responsiveness to KLH, LTA and LPS antigens (Siwek et al . 2010; Sławińska et al . 2011; Siwek et al .…”
Section: Introductionmentioning
confidence: 99%
“…The breed requires minimal veterinary health care, tolerates very low temperatures, is an excellent forager and is reputed to lay eggs low in cholesterol (Krawczyk et al 2005;Krawczyk & Szefer 2012). In recent times, it has been used to study the genetic background of general immune responsiveness to KLH, LTA and LPS antigens (Siwek et al 2010;Sławi nska et al 2011;Siwek et al 2012).…”
Section: Introductionmentioning
confidence: 99%